Artificial intelligence and national security - Montasari, Reza (Springer eBook Collection, 2022)
1. Artificial Intelligence and the Spread of Mis- and Disinformation -- 2. How States’ Recourse to Artificial Intelligence for National Security Purposes Threatens Our Most Fundamental Rights -- 3. The Use of AI in Managing Big Data Analysis Demands - Status and Future Directions -- 4. The Use of Artificial Intelligence in Content Moderation in Countering Violent Extremism on Social Media Platforms -- 5. A Critical Analysis into the Beneficial and Malicious Utilisations of Artificial Intelligence -- 6. Countering Terrorism: Digital Policing of Open Source Intelligence and Social Media Using Artificial Intelligence -- 7. Cyber Threat Prediction and Modelling -- 8. A Critical Analysis of the Dark Web Challenges to Digital Policing -- 9. Insights into the next generation of Policing: Understanding the impact of technology on the police force in the digital age -- 10. The Dark Web and Digital Policing -- 11. Pre-emptive policing: Can technology be the answer to solving London’s knife crime epidemic?.